REFORMULATION OF THE PRELIMINARY EVIDENCE AUDIT TYPE IN TAXATION: WHEN LEGAL HERMENEUTICS MEETS THE RULE OF LAW (Part 1 of 2) - Henry D. P. Sinaga; Denny Irawan (Scientia Integritas Utama, 2022)
The existence of facts in the form of two pretrial decisions decided that the two preliminary evidence examinations were invalid and declared null and void. It needs to address the shift in meaning that led to this type of preliminary evidence examination. Two conclusions can be drawn based on the legal hermeneutics method, which is framed within the framework of the rule of law. First, there has been a shift in the meaning of preliminary evidence examination contained in the KUP Law, namely the existence of a closed type of preliminary evidence audit in Government Number 74 of 2011 and PMK Number 239/PMK.03/2014. This meaning can be a problem in terms of tax enforcement that must be proportional to upholding legal certainty, public benefits, and justice, and in terms of administering government administration which must be based on the principle of legality, the focus of protection of human rights, and the general direction of good governance. Second, the reformulation of preliminary evidence audit must be carried out by eliminating the prevailing type of closed preliminary evidence audit. As the understanding and explanatory side of legal hermeneutics has defined preliminary evidence examination as a series of activities carried out by preliminary evidence auditors against individuals and or entities related to circumstances, actions, and/or evidence that can provide indications of a strong suspicion that a crime in the taxation sector is being or has occurred and can cause losses to state revenue. It is necessary to delete the legal text related to the type of closed preliminary evidence audit in a secure manner.